Implementasi Cerita Islami dalam Menanamkan Nilai-nilai Keagamaan pada Santri Taman Pendidikan Al-Qur’an - Simamora, Mukmin Ridoan; Sujatmiko, M.; Kamila, Faizah; Rismawati, Yanda (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
The phenomenon of moral degradation and the weakening of religious character in children during the digital era has become an increasingly concerning issue. Many children are more familiar with gadgets and digital content than with religious values, a crucial foundation in character formation. This study examines the implementation of Islamic stories as an effective method for shaping children's religious character. The research method used in this study is descriptive qualitative. Data collection techniques included observation, in-depth interviews, and documentation. The research results reveal three main findings: first, the process of implementing Islamic stories; second, the religious values instilled; and third, the challenges faced. Islamic stories have become a routine part of the learning process, conducted monthly during the third week and inserted outside the main learning time. The religious values instilled include monotheism (tauhid), worship (ibadah), and morality (akhlak). Challenges in implementing Islamic stories include limited story sources, difficulty selecting appropriate stories, and limited learning time. The implications of this study indicate that the structured implementation of Islamic stories, adapted to children's age, is proven to be effective in instilling religious values and serves as an educational alternative amidst the increasingly complex challenges of the times.